2014
DOI: 10.1021/ie502584m
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Thermal Stability, Flame Retardancy, and Antimicrobial Properties of Cotton Fabrics Functionalized by Inorganic Nanocomposites

Abstract: In this investigation, various metal oxide (ZrO2, MgO, TiO2) nanoparticles were prepared using the hot-air spray pyrolysis method. The prepared nanoparticles were characterized using the X-ray diffraction (XRD) technique, scanning electron microscopy (SEM), and transmission electron microscopy. The colloidal silica (SiO2) sol was prepared using the sol–gel method, mixed with various metal oxides (ZrO2, MgO, TiO2). Uncoated cotton fabrics were separately impregnated with the prepared nano­(composite) sols follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…It was found that carbon–TiO 2 /ZnO has a stronger antimicrobial effect than a TiO 2 /ZnO nanocomposite, and the growth of E. coli on the control plate decreased after ultraviolet irradiance . Rajendran et al prepared cotton fabrics impregnated with zirconium dioxide (ZrO 2 ), magnesium oxide (MgO), and TiO 2 NP sols, which are colloidal silica (SiO 2 ) mixed with metal oxides, and compared their thermal, flame retardance and antimicrobial properties . ZnO/SnO 2 (tin oxide) hybrid nanostructure films were prepared to enhance the antibacterial activity against Gram‐negative E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that carbon–TiO 2 /ZnO has a stronger antimicrobial effect than a TiO 2 /ZnO nanocomposite, and the growth of E. coli on the control plate decreased after ultraviolet irradiance . Rajendran et al prepared cotton fabrics impregnated with zirconium dioxide (ZrO 2 ), magnesium oxide (MgO), and TiO 2 NP sols, which are colloidal silica (SiO 2 ) mixed with metal oxides, and compared their thermal, flame retardance and antimicrobial properties . ZnO/SnO 2 (tin oxide) hybrid nanostructure films were prepared to enhance the antibacterial activity against Gram‐negative E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…However, cotton functionalized with different ionic liquids does not flame during and after the removal of the flame. The coated CO slowly ignitesthe flame and keeps burn slowly for 173s (see [14,15].…”
Section: Flame Retardancymentioning
confidence: 99%
“…The detrimental effects of bacteria can be mitigated via the use of a broad‐spectrum antimicrobial finishing agent in the treatment of textiles. The incorporation of antibacterial moieties into fabrics has been widely adopted and is typically achieved via either chemical or physical treatment, such as the incorporation of metal and metal oxide nanoparticles (Fu et al, ; Goli et al, ), nanocomposite particles (Rajendran et al, ), organic quaternary ammonium salts (Lu et al, ; Yu et al, ), guanidine (Li et al, ), chitosan (Feng et al, ), and so on. Therefore, considerable progress has recently been made in terms of the development of antibacterial fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of antibacterial moieties into fabrics has been widely adopted and is typically achieved via either chemical or physical treatment, Supporting information Additional supporting information may be found online in the Supporting Information section at the end of the article. such as the incorporation of metal and metal oxide nanoparticles (Fu et al, 2015;Goli et al, 2013), nanocomposite particles (Rajendran et al, 2014), organic quaternary ammonium salts (Lu et al, 2007;Yu et al, 2015), guanidine (Li et al, 2017), chitosan (Feng et al, 2016), and so on. Therefore, considerable progress has recently been made in terms of the development of antibacterial fabrics.…”
Section: Introductionmentioning
confidence: 99%